(untitled) (Indian Journal of Arid Horticulture, 2013)
Low calorie blended RTS beverages of Indian gooseberry and Kinnow were prepared by replacing sucrose with artificial sweeteners Acesulfame -K and Sucralose. The treatments were analyzed for sensory quality and physico-chemical attributes, at monthly interval during storage for three months at refrigerated temperature. Treatments significantly affected the taste and overall sensory quality of the beverages. Sensory quality of the beverages decreased with the storage intervals. Use of acesulfame-K and sucralose in 25:75 proportions had an overall sensory score of 5.86/9.00 at the end of the storage period of 90 days, which was at par with that in RTS beverage sweetened by cane sugar (6.06/9.00). TSS, acidity and total sugar increased, while ascorbic acid and total phenol decreased with the advancement of storage period. The sugars content in the freshly prepared aonla- Kinnow RTS beverages having cane sugar was 9.58 per cent but in the same RTS having acesulfame- K and sucralose (25:75 ratio) was 1.03 per cent only. It was observed from this research that the low calorie beverages sweetened with 25% Acesulfame- K and 75% sucralose were found optimum regarding sensory characteristics.